Development of Students’ Book Based on Science, Technology, and Society with Integration Life Based Learning in Biotechnology Material in The XII Grade - Nury Qurrota Ayun; Suratno Suratno; Erlia Narulita (Pancaran Pendidikan, 2018)
Learning is organized not only to make learners have cognitive skills, but also to have the skills to apply in their life. Biotechnology is one of the areas of science that requires special skills in its application. Efforts that can be made to have skills in biotechnology applications can use quality teaching materials, that is student books. This research is a development research and using 4D model consisting of four stages but in this research only consist of three stages (define, design, and develop). The value of the validity of the books of students who developed 89.27% with the category is very valid. The average score of test book readability of students is 91,85% with very good category. The practical value of the book is 98.33% with very practical category. These results indicate that the developed student book is valid and practical for use in biotechnology learning in grade XII SMA.